Comparison of potentiality of Zinc oxide nanoparticles and hydrogen peroxide in removal of hexavalent chromium from polluted water - Anvar Asadi; Mohammad Hadi Dehghani; Noushin Rastkari; Simin Nasseri; Amir Hossein Mahvi (مجله دانشگاه علوم پزشکی بیرجند, 2012)
Background and Aim: Common sources of chromium in wastewater are electroplating and leather industries. Thus, the present study aimed at investigating and comparing between chemical (H2O2) method and nano-photocatalytical(UV/ZnO) method in removing of Cr(VI) from polluted water. Materials and Methods: In this experimental-analytical study, effective factors on reduction process such as ZnO (0.05–0.15 g/L) , H2O2 (0.5-1.5 mol/L) for UV/H2O2 process and pH(5-9) were investigated. The initial concentration of the substrate was taken 0.1-15mg/L.Stock chromate (V:6) solution was prepared through dissolving Potassium dichromate (K2Cr2O7) in originally distilled water. Residual concentrations of Cr(VI) were measured spectrophotometrically at 540nm. Results: The results indicated that with increasing reduction agent concentration and decreasing pH, the removing efficiency increased. For low initial concentrations of Cr(VI) photocatalytic process was more effective than the chemical one, but for high initial concentration the result was the opposite.In the present study, using of these procedures was applied to natural water samples. Conclusion: The results of this study indicated that H2O2 as a cheap and available agent and also UV/ZnO, as a friendly and without residual environmental treatment process, can be used for effective reduction of Cr(VI) to yield Cr(III).